An Analysis of Code Mixing Used in Opinion Rubric of Kompas Newspaper - Syafryadin, Syafryadin; Rahmawati, Istiqomah Nur; Febriani, R Bunga (English Education: Jurnal Tadris Bahasa Inggris, 2020)
This study investigated the kinds of code mixing used and its meaning at opinion rubric in kompas newspaper. The research question of this study was what kinds of code mixing used and its meaning at opinion rubric in kompas newspaper. The writer took 15 samples of opinion. Rubric in March 2018. The design of this study is descriptive qualitative. In this study, the writer analyzed the data through the following steps: 1) Morphological analysis: first, the writer identified the English code mixings in word, phrase, clause, idiom and reduplication insertions which consisted of one or more morphemes and then analyzed them based on morphological aspects. Finally, the writer classified the morphological process of the words whether it included inflectional or derivational morphemes. 2) Semantic analysis: the writer interpreted the meaning of English code mixings in word, phrase, clause, idiom and reduplication insertions based on the context of the sentence. The result of this study shows that there are five kinds of code mixings that used in the newspaper, namely code mixing of word insertion that consists of 36 data, phrase insertion consists of 56 data, clause insertion consists of 6 data, idiom or expression insertion consists of 15 data, and reduplication insertion consists of 1 data. The code mixings in phrase insertion are most frequently used in newspaper rather than the other kinds of code mixings, while the most rarely used is code mixing in reduplication insertion.